Successful and unsuccessful attempts to resolve caribou management and timber harvesting issues in west central Alberta - Hervieux, David; Edmonds, Janet; Bonar, Richard; McCammon, Jim (Rangifer, 1996)
Research studies of woodland caribou in west central Alberta began in 1979 in response to proposed timber harvesting on their winter ranges. Using results from initial studies, timber harvest guidelines were developed. A recent review of these guidelines, and the assumptions on which they were based, has resulted in a renegotiation by government and industry of timber harvesting on caribou range in west central Alberta. Caribou range in west central Alberta overlaps many jurisdictional boundaries: federal and provincial lands, four Forest Management Agreement Areas, three Alberta Land and Forest Service Regions and two Alberta Fish and Wildlife Service Regions. This jurisdictional complexity in combination with other factors such as total allocation of the timber resources, high levels of petroleum, natural gas and coal extraction activities, a high level of concern by public groups for caribou conservation and recent understanding of woodland caribou needs for abundant space has made resolution of caribou/timber harvest conflicts exceedingly slow and often relatively unproductive. This paper reviews 10 years of trying to resolve conflicts between timber harvesting and caribou conservation through meetings, committees, integrated resource planning, policy papers and public consultation. We describe what might be learned by other jurisdictions that are trying to resolve similar caribou/timber harvesting issues. We conclude with an overview of recent timber harvest planning initiatives on caribou range in west central Alberta.